LEMBAR KERJA SISWA (LKS) BERTAMPILAN KOMIK PADA MODEL PEMBELAJARAN CHILDREN LEARNING IN SCIENCE (CLIS) UNTUK MENINGKATKAN KETERAMPILAN PROSES SAINS SISWA - Felisia Hilda Asmi; Yohanes Kurniawan; Bernardus Tube; Ricardus Jundu (JOURNAL OF KOMODO SCIENCE EDUCATION, 2018)
Comic-style Student Worksheets (LKS) are worksheets that contain information and instructions from the teacher to students to work on a particular experiment presented by displaying comics while illustrated student worksheets are student worksheets that provide information and instructions from the teacher to students to work on one specific experiment presented with pictures. The use of LKS in this study is supported by applying the CLIS learning model that is a learning model that seeks to develop students' ideas or ideas based on the results of observations or experiments using LKS. The purpose of this study was to find out whether there were significant differences in science process skills between students taught using comic-style LKS on the CLIS learning model with students taught using illustrated worksheets in the CLIS learning model and to find out whether students' science process skills were taught using comic LKS on the CLIS learning model is higher than the students taught using illustrated worksheets in the CLIS learning model. The sample of this study was students of class VIII A as the experimental class and class VIII B as the control class, with the research design Randomized Control Group Only Design and the research instruments used were text LKS, comic-style LKS, illustrated worksheets and observation sheets of students' science process skills. From the results of data analysis using the t-test, obtained: 1) there are significant differences in science process skills between students taught using comic-style LKS on the CLIS model with students taught using illustrated LKS on CLIS; 2) science process skills students taught using comic-style LKS on the CLIS learning model are higher than students explained using illustrated worksheets in the CLIS learning model.